'Out of Proportion to the Small Loss': Productivist Agriculture in the Farming Novels of John McGahern and Halldór Laxness. Issue 1 (May 2019) - Dennis, Ryan
Abstract : Ireland and Iceland, both (semi-)peripheral islands in relation to Europe's core hegemonic capitalism, once shared similar farming systems based on small holdings and rotational grazing. Today, however, agriculture looks increasingly different in each nation, for at critical junctures their agriculture policy decisions took radically divergent paths. This paper will examine Irish writer John McGahern's That They May Face the Rising Sun and the Icelandic novel Independent People by Hálldor Laxness as farming novels that ultimately stand as responses to these agricultural policies during the periods they were made. It will contend that, given each author's experience in farming, the novels must be read as acts of political intent meant to provide warnings against productivist policies and the loss of social and rural capital they generate. In connecting these works to the specific agricultural policies enacted and practiced at the time of their writing, a form of resistance will be brought to light that has been overlooked thus far in their registration as world literature.